La littératie en voie de changement : respect du genre et jonctions interpropositionnelles dans des lettres à des professionnels du droit sur Internet - Soili Hakulinen; Meri Larjavaara (Discours)
The article deals with conventions of written French. Democratization of writing – every speaker writes and everyone can publish texts on the Internet – is seen as a catalyst for the change of norms of written French. To investigate this phenomenon we analyse letters published on an online legal advice forum. The letters are written by Internet users to professional lawyers. They are clearly coherent and follow a certain structure. Some of their characteristics pertain to standard written French while others do not. In our study, we concentrate particularly on junctions between propositions. These junctions have an important role in cohesion. By taking advantage of notions introduced by Raible (1992; 2001), we study the integrative features of the text and its density. It seems that the discursive genre in question lies at the crossroads of two almost opposite tendencies: the density found in standard written French is confronted with less dense linguistic features.